Eu estou nos Axés: relações de hierarquias e reciprocidades estabelecidas nos Candomblés - Talga, Jaqueline Vilas Boas (2013)
The origin, expansion and restructuring of Candomblés are presented as a way of analyzing the changes and differentiated relations between people involved in this religiosity. Empirically, and more specifically, we follow the lineage of the family candomblé queto do Axé Oxumarê. We depart from Uberlândia-MG, going trough São Paulo-SP finally reaching the original house in Bahia. The main method adopted in this research was that of participant observation. We found complex relations of hierarchy and reciprocity within all social relations established in this religiosity. We found different changes in the interior of the family and along the lineage regarding teaching, the concept of the ritual times, the prevalence of some rituals over others, the relations of gender and the absorption of practices, mainly of other African religiosities. All these structural changes allowed us to think the changes in the treatment given to the different categories of people in the Candomblés. By recognizing the differentiations existing in this religious field, we aim at contributing critically with the observations of this religiosity. In doing so, we support the povo de santo (adepts) against the general attacks they suffer because of their way of adoring the sacred.